Contralateral synaptic changes following severe unilateral brain injury - Yuan Zhuang; Jinqian Dong; Qianqian Ge; Bin Zhang; Mengshi Yang; Shenghua Lu; Hao Li; Fei Niu; Xiaojian Xu; Baiyun Liu (Brain Research Bulletin, 2022)
The brain is highly integrated and thus unilateral injury can impact the contralateral hemisphere. However, further research is needed to clarify the changes in the response of the contralateral homotopic area to ipsilateral injury. We hypothesized that severe unilateral brain injury would be accompanied by contralateral synaptic changes that are related to functional recovery. To test this, we divided rats into sham and experimental groups. In the experimental group, we performed right motor cortex resection. These rats were further divided into three subgroups according to post-injury time: 7 days, 14 days, and 30 days post-injury. Rats in each group were evaluated using a beam walking test to quantify the recovery of motor function, and all rats received an injection of adeno-associated virus-containing green fluorescent protein (GFP). Finally, we conducted morphological and histological analyses to identify synaptic changes. Over time, the behavior of the rats that underwent right motor cortex resection recovered. Furthermore, in contrast to the sham group, the experimental groups exhibited an increase in the spine density and expression of synaptic proteins in layer V of the contralateral motor cortex, which was consistent with the GFP-labeled neurons. Moreover, more immature spines were observed 7 days post-injury. Notably, spine morphology matured from 7 to 30 days, and the increase in Synapsin-1 intensity in layer V peaked 14 days after the resection, whereas PSD-95 intensity continued to increase until day 30. Our findings suggested that following motor function recovery from unilateral brain injury, spine morphology and synaptic proteins change dynamically in the contralateral hemisphere.